Free Piston Stirling Engine as a new heat recovery option for an Internal Reforming Solid Oxide Fuel Cell. (June 2021) - Majidniya, Mahdi; Remy, Benjamin; Boileau, Thierry; Zandi, Majid
Abstract: Energy demand increment besides the reduction of fossil fuel resources from one side, and climate issues concerning the conventional power production methods from another side lead humanity to more efficient and cleaner power production methods. One of these methods is polygeneration microgrids based on a renewable energy source. In the present study, a combined cycle of a Free Piston Stirling Engine with a Permanent Magnet Linear Synchronous Machine was proposed as a new heat recovery option for the high-quality thermal energy of an Internal Reforming Solid Oxide Fuel Cell as electricity. Then, a Double Effect Absorption Chiller and a heat exchanger were used to recover the rest of the heat as cooling and hot water, respectively. After modeling and validating all the systems, they were combined. The results of the combined system showed 31.7% (or 40% by including cooling production of Double Effect Absorption Chiller instead of its heat consumption for efficiency calculation) of total efficiency improvement compared to the standalone Internal Reforming Solid Oxide Fuel Cell. Furthermore, the electrical efficiency of the system was improved by 14.1%. Graphical abstract: Image 1 Highlights: A nonlinear thermodynamic model of a β-type FPSE is developed and validated. A PMLSM is modeled, coupled with the FPSE, and the combined system is controlled. An IRSOFC and a Double Effect Absorption Chiller (DEACH) are modeled and validated. A tri-generation microgrid, including an IRSOFC, an FPSE, a PMLSM, and a DEACH is studied. The proposed system produces electricity, heating, and cooling with an efficiency of around 64%.